5 Plus 1 : Printing Sdn. Bhd. / Khirul Amir Mat Saad ... [et al.] - Mat Saad, Khirul Amir; Sharkawi, Shariza; Nasir, Surani; Abu Bakar, Rahmah; Tahir, Nor Izwani; Mohamed Id, Nuraliza (Faculty of Artistic and Creative Technology, 2003)
Today, printing is become a very important service. Every people will use printing especially for their business, organization and etc. This printing company will help to promote their company or organization service. Furthermore this printing company to give information to people. As the result from our research, we find that printing company has a higher request from people. We hope our business can give satisfy and have a good competeting. Our main target market are production house and production theater. We also give our service for IPT, school and NGO. Our business will give a relevant price to make sure our business in a good situation.